Isolation and characterization of plant growth-promoting rhizobacteria from wild rice (Oryza rufipogon) in the Mekong Delta, Vietnam - NGUYEN TRI YEN CHI; NGUYEN LU KHOI MINH; QUACH VAN CAO THI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chi NTY, Minh NLK, Thi QVC. 2025. Isolation and characterization of plant growth-promoting rhizobacteria from wild rice (Oryza rufipogon) in the Mekong Delta, Vietnam. Biodiversitas 26: 1221-1228. Rhizospheric bacteria play a very crucial role in crops, especially rice. In contrast to cultivated varieties, wild rice (Oryza rufipogon), which is abundantly found in Mekong Delta canals, may have distinct rhizobacterial populations. Therefore, the objective of this work was to isolate and characterize Plant Growth-Promoting Rhizobacteria (PGPR) from wild rice with the characteristics of nitrogen fixation, phosphate solubilization, and IAA synthesis. A total of 12 bacterial strains, including seven bacterial strains of nitrogen-fixation and five strains of phosphate-solubilizing microbes, from four rhizospheric soil samples of wild rice in Tien Giang and Vinh Long provinces of the Mekong Delta, Vietnam. The results showed that strain B?1.2 had the highest nitrogen fixation activity with NH4+ content of 0.281±0.007 mg/L. In contrast, strain B?1.3, had the highest phosphorus solubilizing ability with a halo diameter of 1.123 ± 0.025 mm. Also, the finding showed that six out of twelve bacterial strains were capable of synthesizing IAA (Indole-3-Acetic Acid), of which strain B?2.3.1 produced the highest IAA with a concentration of 0.053 ± 0.001 mg/L after 8 days of bacterial inoculation. In particular, B?2.3.2, B?1.3, and B?2.4 simultaneously exhibited the ability of nitrogen fixation, phosphate solubilization, and IAA synthesis. The strain B?1.3 was identified as Stenotrophomonas sp. based on colony morphology, biochemical characteristics, and 16S rRNA gene sequencing with 91.74% similarity. To our knowledge, this is the first report of isolation of rhizospheric bacteria from O. rufipogon with the characteristics of nitrogen fixation, phosphorus solubilization, and IAA production in the Mekong Delta, Vietnam.